2019
DOI: 10.35940/ijitee.l2984.1081219
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Municipal Solid Waste Disposal on the Engineering Properties of Soil from a Non-Engineered Landfill

Abstract: The presents study showed the effect of open dumping on soil characteristics and biodegradation settlement analysis of soil in non-engineered landfill. The contaminated soil is referred to as waste soil which has different settlement rates due to the various categories and complex characteristics of waste. The degradation of waste causing percolation of leachate into soil affecting the strength and stability of soil. This paper includes the analysis of geotechnical properties and settlement analysis of waste s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 12 publications
0
0
0
Order By: Relevance
“…The organic waste percentage in these areas of Himachal Pradesh was 57.67% (Solan), 52.83% (Sundernagar), 56% (Mandi), and 50.83% (Baddi). Also, Thakur et al, [23] obtained high organic content in waste, 56.1%, which mostly consisted of food, kitchen and vegetable waste, and 10.3% of plastic waste. In addition, U. K. Singh et al, [8] indicated similar results, they showed high organic and earth material components, 72% and 13.40%, respectively.…”
Section: Municipal Solid Waste (Msw) Composition In Disposal Sitesmentioning
confidence: 98%
See 4 more Smart Citations
“…The organic waste percentage in these areas of Himachal Pradesh was 57.67% (Solan), 52.83% (Sundernagar), 56% (Mandi), and 50.83% (Baddi). Also, Thakur et al, [23] obtained high organic content in waste, 56.1%, which mostly consisted of food, kitchen and vegetable waste, and 10.3% of plastic waste. In addition, U. K. Singh et al, [8] indicated similar results, they showed high organic and earth material components, 72% and 13.40%, respectively.…”
Section: Municipal Solid Waste (Msw) Composition In Disposal Sitesmentioning
confidence: 98%
“…MSW compositions vary based on its types and sources [14,23]. Food and garden wastes, plastics, paper products, textiles, rubber, wood, ashes, and soils are common MSW components [29,30].…”
Section: Municipal Solid Waste (Msw) Composition In Disposal Sitesmentioning
confidence: 99%
See 3 more Smart Citations